HGG-01. A novel genetically engineered H3.3G34R model reveals cooperation with ATRX loss in upregulation of PRC2 target genes and promotion of the NOTCH pathway. (3rd June 2022) - Abdallah, Aalaa; Cardona, Herminio; Gadd, Samantha; Brat, Daniel; Picketts, David; Becher, Oren; Li, Xiao-Nan
Abstract: BACKGROUND: Pediatric high-grade gliomas (pHGGs) are an aggressive CNS tumor which are often characterized by mutations in H3F3A, the gene that encodes Histone H3.3 (H3.3). A substitution of the Glycine at position 34 of H3.3 with either Arginine or Valine (H3.3G34R/V), was recently described in a large cohort of pHGG samples and has been characterized as occurring in anywhere between 5-20% of pHGGs. Attempts to study the mechanisms of H3.3G34R have proven difficult due to the developmental nature of the disease and the requirement of co-occurring mutations for model development. METHODS: We utilized the RCAS system to develop a genetically engineered mouse model (GEMM) that incorporates PDGF-A activation, TP53 loss and the H3.3G34R mutation both in the context of ATRX loss and ATRX presence in nestin expressing progenitors. RESULTS: We show that in H3.3G34R expressing mice, ATRX loss significantly increased tumor latency from 90 days to 143 days (p < 0.01, Log rank test) and decreased tumor incidence from 81% to 57% (p < 0.01, Fisher's exact test). By contrast, H3.3G34R did not significantly impact tumor latency in either our ATRX loss (163 days to 143 days, p = 0.178, Log-rank test) or our ATRX expressing (95 days to 90 days, p = 0.415, Log-rank test) models. Transcriptomic analysis revealed that ATRX loss in the context of H3.3G34R upregulates the PRC2 associated genes Hoxa2, Hoxa3, Hoxa5, and Hoxa7 (p < 0.05, unpaired t-test). GSEA analysis and RT-qPCR data suggest that ATRX loss works synergistically with H3.3G34R to promote NOTCH pathway activation through upregulation of the NOTCH ligand Dll3 (p < 0.01, unpaired t-test). CONCLUSIONS: Our study proposes a model in which ATRX loss is the major contributor to transcriptomic changes in the majority of H3.3G34R pHGGs. Broadly, our work highlights the importance of studying mechanisms of co-occurring genetic events separately and in combination.